Effect of Giving Api-Api (Avicennia marina ) Mangrove Leaf Solution In Artificial Feed On The Immunity Response and Growth of Vannamei Shrimp (Litopenaeus vannamei) - Linayati, Linayati; Rattanavichai, Wutti; Mardiana, Tri Yusufi; Nugroho, Leonardus Bayu; Yahya, Muhammad Zulkham (Journal of Aquaculture and Fish Health, 2024)
The purpose of this study was .to determine the effect of giving Avicennia marina mangrove leaf solution on artificial feed to increase the immune response and growth of vannamei shrimp. The parameters observed in this study were the enhancement of PA value (Phagocytosis Activity), ADG (Average Daily Growth), FCR (Feed Conversion Ratio), and EPP (Efficiency of Feed Utilization). The vannamei shrimp used was PL-20 fry with the weight of 1,09 – 1,13 gâ‹…head-1 and density 1 shrimp L-1. The method used in this study was an experimental method in the laboratory, with a completely randomized design (CRD) with 4 treatments and 3 replications. This research was conducted by adding Avicennia marina mangrove leaf solution to the feed, with treatments of A (control), B (125 "°), C (175 "°), and D (225 "°). The addition of Avicennia marina leaf solution to the feed had a significant effect on the increase of phagocytosis activity and growth of the shrimp with F count of 30,773 which was higher than the F table of 4,06. Moreover, the best dose obtained in treatment D which resulted in an increase in PA was 61,9%, ADG was 0,22 gâ‹…day-1, FCR was 1,29, and EPP was 79,04%.